Analisis Perbandingan Kinerja Keuangan Setelah Merger atau Akuisisi - Akhbar, Rizky Trinanda; Nurdin, Ali; Maspupah, Ulfa Siti (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p13, 2021)
This study aims to investigate the company's financial performance before and after a merger or acquisition process. The research focuses on the financial performance of companies listed in Indonesia Stock Exchange that did a merger or acquisition in 2012. Secondary data from financial statements was collected and analyzed for four years before and four years after the merger or acquisition. The variables examined are profitability ratios (NPM, ROI, ROA and ROE), activity ratios (TATO and FATO), market ratios (EPS and PER), liquidity ratios (CR and QR) and solvency ratios (DR and DER). Non probability sampling method with a purposive sampling approach is used to determine the samples of this study. Using descriptive statistical test we find that financial performance before a merger or acquisition is fluctuating while after a merger or acquisition tends to decline. In other words, merger and acquisition not effective yet to improve company’s financial performance. Keywords: Acquisition; Financial Performance; Merger.